Heroic Speech Portrait from the Point of view of Linguistics (On the Example of the Works of the Utkir Khoshimov) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the semantic units that create the image in the stories of Utkir Hoshimov. It is evidenced that the author was able to create a character using linguistic units, to use various language tools to create a memorable and vivid character image, to deepen the psyche of characters, to use various details, images of natural phenomena, external factors addressed in order to fill his character.